Colon-targeted delivery of cyclosporine A using dual-functional Eudragit® FS30D/PLGA nanoparticles ameliorates murine experimental colitis - Naeem M (Dove Medical Press, 2018)
Muhammad Naeem,* Junhwan Bae,* Murtada A Oshi, Min-Soo Kim, Hyung Ryong Moon, Bok Luel Lee, Eunok Im, Yunjin Jung, Jin-Wook Yoo College of Pharmacy, Pusan National University, Busan, Republic of Korea *These authors contributed equally to this work Background: Colon-targeted oral nanoparticles (NPs) have emerged as an ideal, safe, and effective therapy for ulcerative colitis (UC) owing to their ability to selectively accumulate in inflamed colonic mucosa. Cyclosporine A (CSA), an immunosuppressive agent, has long been used as rescue therapy in severe steroid-refractory UC. In this study, we developed CSA-loaded dual-functional polymeric NPs composed of Eudragit® FS30D as a pH-sensitive polymer for targeted delivery to the inflamed colon, and poly(lactic-co-glycolic acid) (PLGA) as a sustained-release polymer.Methods: CSA-loaded Eudragit FS30D nanoparticles (ENPs), PLGA nanoparticles (PNPs), and Eudragit FS30D/PLGA nanoparticles (E/PNPs) were prepared using the oil-in-water emulsion method. Scanning electron microscope images and zeta size data showed successful preparation of CSA-loaded NPs.Results: PNPs exhibited a burst drug release of >60% at pH 1.2 (stomach pH) in 0.5 h, which can lead to unwanted systemic absorption and side effects. ENPs effectively inhibited the burst drug release at pH 1.2 and 6.8 (proximal small intestine pH); however, nearly 100% of the CSA in ENPs was released rapidly at pH 7.4 (ileum–colon pH) owing to complete NP dissolution. In contrast to single-functional PNPs and ENPs, the dual-functional E/PNPs minimized burst drug release (only 18%) at pH 1.2 and 6.8, and generated a sustained release at pH 7.4 thereafter. Importantly, in distribution studies in the gastrointestinal tracts of mice, E/PNPs significantly improved CSA distribution to the colon compared with PNPs or ENPs. In a mouse model of colitis, E/PNP treatment improved weight loss and colon length, and decreased rectal bleeding, spleen weight, histological scoring, myeloperoxidase activity, macrophage infiltration, and expression of proinflammatory cytokines compared with PNPs or ENPs.Conclusion: Overall, this work confirms the benefits of CSA-loaded E/PNPs for efficiently delivering CSA to the colon, suggesting their potential for UC therapy. Keywords: cyclosporine A, ulcerative colitis, colon-targeted nanoparticles, sustained and pH-sensitive release